Pitch Lake. Trinidad - (:unkn) unknown (My University, 2010)
Here is a photograph of the pitch lake with one of Trinidad’s native palms, Acrocomia ierensis, growing in the lake. What appears to be a pattern on the lake is really pools of water and the blurred areas of the photograph might be the result of water evaporating from the surface of the lake. The horizon is covered with trees from end to end.
Colour: Black and White; Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Asphalt industry--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--La Brea; Forests and forestry--Trinidad and Tobago; Pitch; 1954; Palms--Trinidad and Tobago; Trees--Trinidad and Tobago; Pitch Lake, The (La Brea)